Melting enhancement in vertical triplex-tube latent heat thermal energy storage system using BeO nanoparticles and internal fins - Zamira Sattinova; Bakytzhan Assilbekov; Animesh Pal; Tassybek Bekenov; Bidyut Baran Saha (Results in Engineering)
This study presents the application of internal fins and beryllium oxide (BeO) nanoparticles to accelerate the melting of lithium chloride as a phase change material (PCM) encapsulated in a latent heat thermal energy storage unit which is an intermediate element in a nuclear power plant's assisted thermal energy systems. The transient melting behavior of PCM is numerically investigated in 2D planar geometries using the enthalpy-porosity model. A particular effect of fins, BeO nanoparticles, and a combination of both at different volume fractions on melting performance is analyzed. The thermal conductivity of PCM is enhanced by around 15 % for both liquid and solid phases at a 5 % volume fraction of BeO nanoparticles. Employment of 2, 4, and 6 fins is seen to improve melting time by 30.6 %, 44.4 %, and 52.8 %, respectively, as compared to a base case. Simulation results also have shown that adding 1 %, 3 %, and 5 % BeO nanoparticles by volume in the PCM reduced the melting time by 2.8 %, 7.2 %, and 12.2 %, respectively, relating to the base case. Adding 5 % BeO nanoparticles by volume in the PCM results in a melting time decrease of 38.9 %, 51.1 %, and 58.3 % taking pure PCM case as the reference, respectively, for 2, 4, and 6 finned cases. Analysis of simulation results revealed that the effect of fins on melting time at a 5 % volume fraction of BeO nanoparticles weakens as the fin number increases. Comparative analysis has shown that adding BeO nanoparticles demonstrates melting acceleration by 4.3 % compared to Al2O3 nanoparticles.